Crescimento de nanopartículas metálicas mistas em substrato de sílica visando a produção de sensores ópticos - Pereira, Amanda Figueiredo (2019)
Nanoparticles (NPs) are materials that are on the nanometer scale, and are exhibiting different physical and chemical properties of their extended solid. For its properties to be distinct the nanoparticles necessarily have to be below their critical size, being necessary the control and the maintenance of its size as well as its morphology, so that we can propose a viable application for these materials. For the synthesis of nanoparticles there are methods that allow obtaining materials that can have modified and improved properties, and can be used, for example, in improving the sensitivity of optical sensors. The present work consists of depositing different concentrations of gold and silver nanoparticles on a silica substrate, in order to obtain a model system for a future application in optical fiber based sensors. The samples were synthesized by two different methods: the chemical and the thermal. When comparing the films formed on the coverslips used as substrate, it is possible to visualize a great difference in the characteristics presented by the samples obtained by each of the methods, indicating a difference in the plasmon band. In addition, the samples were separated into three groups for the study on the properties of the mixture between gold and silver nanoparticles. The first group consisted of the deposition of gold NPs and the deposition of silver NPs at a later stage. The second group consisted in the deposition of silver NPs and then in the deposition of gold. And finally, the third group consisted of the joint deposition of the mixture of the two metals. In addition to the difference between the depositions, some of the samples were anchored with the europium(III)-β-diketonate complex to investigate the interaction between the plasmon resonance of the NPs and the fluorescence of the complex. For the characterization of all the samples, the absorption spectroscopy in the UV-Vis region, X-ray diffractometry, electron microscopy (TEM and SEM-EDS) and photoluminescence spectroscopy were used. In addition to these analyzes, studies of reproducibility and stability of the films were also made. The nanoparticles of the three groups obtained by the chemical and thermal method are spherical, with only one of the groups showing cubic NPs. The variation by both the reduction and the deposition methods affects the size of the NPs, ranging from 3.7 to 6.9 nm. The plasmon bands of the methods and the groups diverge among themselves, evidencing that the proposed routes interfere in the result of the synthesis of the nanoparticles. As for the samples covered with the complex, there was a displacement of the band evidencing its interaction with the sample. Through these studies, it can be concluded that these NMs can be used in optical sensors with the function of increasing the sensitivity of these sensors.